Lower incidence of grade II-IV acute Graft-versus-Host-Disease in pediatric patients recovering with high Vδ2+ T cells after allogeneic stem cell transplantation with unmanipulated bone marrow grafts: a prospective single-center cohort study - Müller, Thilo; Alasfar, Lina; Preuß, Friederike; Zimmermann, Lisa; Streitz, Mathias; Hundsdörfer, Patrick; Eggert, Angelika; Schulte, Johannes; von Stackelberg, Arend; Oevermann, Lena (Frontiers in Immunology, 2024)
Gamma delta (γδ) T cells represent a minor fraction of human T cell repertoire but play an important role in mediating anti-infectious and anti-tumorous effects in the context of allogeneic hematopoietic stem cell transplantation (allo-HSCT). We performed a prospective study to analyze the effect of different transplant modalities on immune reconstitution of γδ T cells and subsets. CD3, CD4 and CD8 T cells were analyzed in parallel. Secondly, we examined the impact of γδ T cell reconstitution on clinical outcomes including acute Graft-versus-Host-Disease (aGvHD) and viral infections. Our cohort includes 49 pediatric patients who received unmanipulated bone marrow grafts from matched unrelated (MUD) or matched related (MRD) donors. The cohort includes patients with malignant as well as non-malignant diseases. Cell counts were measured using flow cytometry at 15, 30, 60, 100, 180 and 240 days after transplantation. Cells were stained for CD3, CD4, CD8, CD45, TCRαβ, TCRγδ, TCRVδ1, TCRVδ2, HLA-DR and combinations. Patients with a MRD showed significantly higher Vδ2+ T cells than those with MUD at timepoints +30, +60, +100 (p<0.001, respectively) and +180 (p<0.01) in univariate analysis. These results remained significant in multivariate analysis. Patients recovering with a high relative abundance of total γδ T cells and Vδ2+ T cells had a significantly lower cumulative incidence of grade II-IV aGvHD after transplantation (p=0.03 and p=0.04, respectively). A high relative abundance of Vδ2+ T cells was also associated with a lower incidence of EBV infection (p=0.02). Patients with EBV infection on the other hand showed higher absolute Vδ1+ T cell counts at days +100 and +180 after transplantation (p=0.046 and 0.038, respectively) than those without EBV infection. This result remained significant in a multivariate time-averaged analysis (q<0.1). Our results suggest a protective role of γδ T cells and especially Vδ2+ T cell subset against the development of aGvHD and EBV infection after pediatric HSCT. Vδ1+ T cells might be involved in the immune response after EBV infection. Our results encourage further research on γδ T cells as prognostic markers after HSCT and as possible targets of adoptive T cell transfer strategies.